2018
DOI: 10.26905/jkdp.v22i2.2092
|View full text |Cite
|
Sign up to set email alerts
|

Initial Effects of Mandatory XBRL Adoption across the Indonesia Stock Exchange`s Financial Information Environment

Abstract: This research aims to investigate the initial effects of mandatory eXtensible Business Reporting Language (XBRL) across the Indonesia Stock Exchange's financial information environment. Financial information environment is measured by event return volatility, absolute cumulative abnormal return, change in standard deviation of returns, abnormal bid-ask spread, and abnormal trading volume. Comparing the effects of pre-and post-XBRL period, we provide evidence that there is no significant implication in the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 28 publications
1
14
0
6
Order By: Relevance
“…In Indonesia, at the beginning of the implementation of XBRL, evidence was found that XBRL had not had a significant effect yet on improving the quality of the financial information environment (Zamroni and Aryani, 2018). Furthermore, the XBRL adoption also did not affect reducing information asymmetry (Tohang et al, 2020), even it had a positive effect in increasing information asymmetry (Jayani et al, 2020).…”
Section: Research Theme 1: Xbrl's Impact On Businessmentioning
confidence: 98%
See 3 more Smart Citations
“…In Indonesia, at the beginning of the implementation of XBRL, evidence was found that XBRL had not had a significant effect yet on improving the quality of the financial information environment (Zamroni and Aryani, 2018). Furthermore, the XBRL adoption also did not affect reducing information asymmetry (Tohang et al, 2020), even it had a positive effect in increasing information asymmetry (Jayani et al, 2020).…”
Section: Research Theme 1: Xbrl's Impact On Businessmentioning
confidence: 98%
“…After observing each selected article by following the XBRL research theme classification guidelines provided by Perdana et al (2015) using XBRL research samples in the international sphere, the results of XBRL research theme classification in Indonesia generally have the same research theme cluster, i.e., i) The influence of XBRL on Business (see, e.g., Jayani et al, 2020;Junus and Irwanto, 2021;(Mahardika andHarahap, 2018) Mayapada, et al, 2020;Pamungkas and Kristanto, 2019;Prasetyo and Apandi, 2019;Saputro and Achjari, 2020;Tohang et al, 2020;Zamroni and Aryani, 2018); ii) Adoption of XBRL (see, e.g., Muchlis et al, 2019); iii) XBRL Engineering Development (see, e.g., Wijanarko and Moedjiono, 2015); and iv) XBRL education such as XBRL teaching and XBRL integration into the accounting curriculum (see, e.g., Wulandari and Ali, 2019;Pujisari and Biyanto, 2019). Table 4 explains the definition and scope of each theme.…”
Section: Stage Three: Research Topics/themesmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, Indonesia has just started designing XBRL taxonomy in 2013. However This phenomenon increases the studies of the issue regarding the mandatory adoption of XBRL, especially in Indonesia, which implemented XBRL in a short time (Zamroni & Aryani, 2018).…”
Section: Introductionmentioning
confidence: 99%